N-3 Polyunsaturated fatty acids alter benzo[a]pyrene metabolism and genotoxicity in human colon epithelial cell models. (February 2019) - Tylichová, Zuzana; Neča, Jiří; Topinka, Jan; Milcová, Alena; Hofmanová, Jiřina; Kozubík, Alois; Machala, Miroslav; Vondráček, Jan
Abstract: Dietary carcinogens, such as benzo[a]pyrene (BaP), are suspected to contribute to colorectal cancer development. n-3 Polyunsaturated fatty acids (PUFAs) decrease colorectal cancer risk in individuals consuming diets rich in PUFAs. Here, we investigated the impact of eicosapentaenoic (EPA) and docosahexaenoic (DHA) acid on metabolism and genotoxicity of BaP in human cell models derived from the colon: HT-29 and HCT-116 cell lines. Both PUFAs reduced levels of excreted BaP metabolites, in particular BaP-tetrols and hydroxylated BaP metabolites, as well as formation of DNA adducts in HT-29 and HCT-116 cells. However, EPA appeared to be a more potent inhibitor of formation of some intracellular BaP metabolites, including BaP-7, 8-dihydrodiol. EPA also reduced phosphorylation of histone H2AX (Ser139) in HT-29 cells, which indicated that it may reduce further forms of DNA damage, including DNA double strand breaks. Both PUFAs inhibited induction of CYP1 activity in colon cells determined as 7-ethoxyresorufin- O -deethylase (EROD); this was at least partly linked with inhibition of induction of CYP1A1, 1A2 and 1B1 mRNAs. The downregulation and/or inhibition of CYP1 enzymes by PUFAs could thus alter metabolism and reduce genotoxicity of BaP in human colon cells, which might contribute to known chemopreventive effects of PUFAs in colon epithelium. Highlights: PUFAs alter metabolism and inhibit genotoxicity of BaP in human colon cell models. DHA and EPA inhibit formation of DNA adducts in colon HT-29 and HCT-116 cells. EPA also reduces levels of markers of DNA damage linked with formation of DNA DSBs. Effects of PUFAs could be partly linked to inhibition of CYP1 expression/activity.